On being different : diversity and multiculturalism in the North American mainstream - Kottak, Conrad Phillip; Kozaitis, Kathryn A. (Boston : McGraw-Hill College, 1999)
Introduction; Culture; From territory; The multicultural society; Ethnicity; Race; Religion; Gender; Sexual orientation...
Includes index.
Keywords: Ethnology; Social structure; North America; Ethnology -- North America; Multiculturalism -- North America; Ethnicity -- North America; Minorities -- North America; Social structure -- North America; North America -- Race relations; North America -- Social conditions